Relationship of Albumin Levels, Comorbidity and Vaccination History with Mortality Of COVID-19 Patients in RSUP. H. Adam Malik Medan - Inez Vania Calandra; Dina Keumala Sari; Bintang Yinke Magdalena Sinaga (Contagion: Scientific Periodical Journal of Public Health and Coastal Health, 2023)
COVID-19 is a type of infectious disease caused by the SARS-CoV-2 virus. According to the results of previous studies, the risk factors for mortality in COVID-19 patients are often found in patients with low albumin levels, patients who have a history of comorbidities and patients who are not vaccinated. This study aims to determine the relationship between albumin levels, comorbidities and vaccination history with the mortality of COVID-19 patients in RSUP. H. Adam Malik Medan. This study used analytic observational with a cross-sectional approach carried out from June 2022-December 2020. Sample data were obtained from RSUP medical records. H. Adam Malik as many as 110 people. Sample data were analyzed using the Chi-Square statistical test. Subjects were male (53.64%), most subjects were ≥ 50 years old (80.91%), moderate subjects (55.45%), severe severity (24.55%) and critical severity (20%). The Chi-Square test showed that there was a significant relationship between albumin levels and mortality (0.003 <0.05). There is no significant relationship between co-morbidities and mortality (0.141 > 0.05). There is a significant relationship between vaccination history and mortality (0.002 <0.05). There is a significant relationship between albumin levels and vaccination history with the mortality of COVID-19 patients in RSUP. H. Adam Malk Medan. Meanwhile, there was no significant relationship between comorbidities and mortality in COVID-19 patients at RSUP. H. Adam Malik Medan. Further research is needed to assess the factors that predict mortality in COVID-19 patients. Keyword: Albumin, Comorbidities, Mortality, Vaccination